Use of Unique Health Identifiers in Universal Health Coverage Programs for Health Insurance Schemes - Dharwadker, Sanjay (World Bank, Washington, DC, 2019)
The World Bank Group (WBG) Data Council endorsed the 2016–2030 Civil Registration and Vital Statistics (CRVS) Action Plan in December 2015. The CRVS plan aims to achieve universal civil registration (CR) of births, deaths, and other vital events for all individuals by 2030. The WBG has been working closely with development partners to provide the requisite support to countries through three interlinked initiatives: the Strategic Action Program for Addressing Development Data Gaps, Identification for Development, and the Global Financing Facility. The WBG recently commissioned country case studies on Colombia, Gabon, Slovenia the Republic of Korea, and Thailand on how the use of a unique identification number (UIN) has facilitated universal health coverage (UHC). The Identification for Development (ID4D) initiative recently published Integrating Unique Identification Numbers In Civil Registration, which provides guidance on options for linking a birth registration number in the civil registration system with the UIN in the national civil identification system. However, there is limited guidance on assigning Unique Health Identifiers (UHIs) in health programs toward the achievement of UHC. This guidance note provides options for assigning UHIs for health programs that are linked to a national (central) system for issuing UINs for a more secure and trusted verification of identities and for health programs in countries without a national unique identification system. Part II describes the importance of UHIs. Part III presents selected country examples of the use of UHIs. Some key governance and technical issues based on country examples are summarized in Part IV. Part V offers recommendations, including an offline option for assigning UHIs for remote areas without Internet connectivity.